SYSTEMATIC REVIEW: THE ENHANCEMENT OF ANTI-INFLAMMATION ACTIVITY OF NON STEROIDAL ANTI-INFLAMMATORY DRUG (NSAID) BY SOLID DISPERSION MODIFICATIONS - RAMADHANI, DHEA A.; YUGATAMA, ADI; ERMAWATI, DIAN E. (International Journal of Applied Pharmaceutics, 2021)
Objective: NSAIDs are very hydrophobic drugs and have low solubility. This causes the bioavailability of NSAIDs to be low in the body thus affect its anti-inflammatory activity. There has been some primary research proven that solid dispersion can increase the solubility and anti-inflammatory activity of NSAIDs. Moreover, there are not researches explaining the effect of a solid dispersion system on the anti-inflammatory activity of NSAIDs. Therefore, it is necessary to conduct a review to assess the effect of the solid dispersion system on the solubility and anti-inflammatory activity of NSAIDs systematically. Methods: This was systematic review research, where the data were originated from PubMed and Science Direct with the keywords ‘NSAID’, ‘solid dispersion’, and ‘drug effect’. The inclusion criteria formulated were English-language papers, published in 2010–2020, and primary research that conducted in vivo anti-inflammatory testing. The appropriate papers by the inclusion criteria were assessed its quality by the SYRCLE’s tool. Data was analyzed narratively. Results: The results were eight papers under the inclusion criteria. As a whole is known modification of solid dispersion can increase the dissolution profile of NSAIDs. This is because the polymer used can increase the wetting of drug particles, thereby being able to increase the solubility of NSAIDs. Conclusion: The anti-inflammatory activity of NSAIDs by solid dispersion systems are increases compared to NSAIDs without solid dispersions.